Energy Efficiency Awareness and Practices Based on Islamic Perspectives - Nurul Hadirah Muszaffarsham; Mohd Zin Kandar; Elina Mohd Husini (Malaysia Institute of Planners, 2024)
Indexed by Scopus/MyCite